Respectable Folly Millenarians and the French Revolution in France and England - Garrett, Clarke (Johns Hopkins University Press, 2019)
Originally published in 1975. The French Revolution generated a wave of popular piety and religious excitement in both France and England, where millenarians-prophets of the millennium-attempted to interpret the Revolution as the fulfillment of the predictions of Daniel and St. John the Divine. This study discusses the millenarian ideal in the context of the intellectual and religious attitudes of the time. Rejecting interpretations of millenarianism that chalk it up to class struggle or mass hysteria, Garrett stresses the interaction between politics and religion, viewing the phenomenon as the interpretation, by a varied assortment of individuals, of coincident political events in eschatological terms. Faced with a change as significant as the French Revolution, people found in the prophetic books of the Bible an understanding of what was happening to them. If the Revolution was God's will, if its development had been foretold, then surely the final outcome would be beneficial, at least for the faithful. Political events became eschatological events, and dangers and misfortunes became simply the chastisements that a fallen world must undergo before the Second Coming of Jesus Christ can redeem it. Although some of the beliefs may now seem bizarre, Garrett shows that, at the time, they attracted many followers for whom these ideas were both reasonable and respectable. Focusing on the careers of three millenarians-Suzette Labrousse, Catherine Théot, and Richard Brothers-Garrett tries to understand these prophets as persons rather than dismiss them as fanatics. Their prominence resulted from their success in transmitting a new political consciousness through familiar religious imagery. While the Revolution gave urgency and tangible reality to millenarian convictions, Labrousse, Théot, and others were convinced, well before the Revolution, that they were the bearers of divine revelations and thus welcomed the Revolution as confirmation of their own missions.